IS IT FORBIDDEN THE WOOD USE OF Araucaria angustifolia? AN ANALYSIS ON THE CURRENT LEGAL BUDGET - Eisfeld, Rozane de Loyola; Arce, Julio Eduardo; Sanquetta, Carlos Roberto; Braz, Evaldo Muñoz (Floresta, 2019)
The objective of this work was to analyze the legal arrangements on a very complex theme in the forest sector: the use of a species threatened with extinction, araucaria. After years of intense deforestation, linked to the country's economic growth, after 1960 decade, it was edited an array of regulations aimed to control the forest use through strict laws and expansion of the environmental bureaucracy. In 2014, MMA Decree 443, araucaria was included in the danger category, restricting any timber use, including the ones gathered under forest management. The justification for this inclusion comes from the population reduction, deforestation and logging. Regarding the justification of its inclusion, it is important to note the non-disclosure of official data, an obligation of the State, on the remaining area and number of individuals. Decree 443 collides with the Brazilian forest low removing rights, as forest management, not established by Law number 12.651 of 2012. It also defies the Complementary Law 140 which establishes reports and technical-scientific studies for framing the listed species. Nor does it comply with the steps required in article 5º MMA Decree 43, which precedes Decree 443. By analyzing the regulations regarding the araucaria and its commercial use: there is no law prohibiting the use, through management and planting; what exists are Decrees and resolutions. Whoever is in the messianic right to forbid the cutting of the species, subsidizes itself in Decrees and resolutions. Moreover, who believes they have the right to cut it, is not aware of the legislation.